Confrontation with influenza - Brydak, Lidia B. (Przewodnik Lekarza/Guide for GPs, 2009)
Every year 5-25% of the world’s population suffers influenza and up to 1 million people die. New cases of the disease and deaths caused by avian flu viruses, which occur in different countries and in different age groups, make it vital for us to implement a suitable policy aimed at decreasing the effects of a possible outburst of pandemic flu. Despite recommendations made not only by the Advisory Committee on Immunization Practices, the American Academy of Pediatrics and 13 international scientific societies, many people still hesitate to use the cheapest and most effective from of prophylaxis, that is, vaccination. In the epidemic season of 2007/08 only 5.6% of the population in Poland was vaccinated, including as little as 1.1% of children aged under 4 and merely 1.9% of children aged 5-14.